Normal physiology. Modul 2 - Sukhomlinova, I.E.; Tichonovskay, M.A.; Voteva, V.E.; Kirsanova, E.V.; Yeryomina, A.K.; Сухомлінова, Ірина Євгенівна; Тихоновська, Марина Анатоліївна; Вотєва, Ванда Євгенівна; Кірсанова, Олена Валентинівна; Єрьоміна, Алла Кузьмівна (Zaporizhzhia state medical university, 2015)
Students’ independent practical work is an important part of the syllabus in the course of Normal Physiology. It helps students to study this fundamental subject. Systematic independent work enables to reach the final goal in the students’ education. It is also important while preparing the students for their future clinical work with patients. These theoretic materials, questions and tests will help students to get ready for the examination.
Нормальна фізіологія. Модуль 2